Rural Unions and Brazil’s Turn to the Right: - Delgado de Carvalho, Priscila (2024)
We analyzed the impacts of the regime change in post-2016 Brazil on patterns of activism, based on the case of the oldest confederation of rural workers in the country. Since the end of the 1990s, the National Confederation of Male and Female Family Farmers (Contag) has concentrated its efforts on demanding public policies for family farming, with the participation of farmers in policy formulation. Using two analytical tools (the differentiation between public and semi-public actions and the modes of gathering), we discussed three moments: the impeachment of Rousseff in 2016, the pension reform between 2016 and 2019, and the COVID-19 Pandemic in 2020. We saw the removal of the Federal government as an interlocutor, efforts to avoid the dismantling of policies, and the return of democracy as a disputed issue.